On the art in the ancient Near East - Winter, Irene. (Culture and History of the Ancient Near East;, 2010)
This volume of collected essays brings together for the first time the range of Winter's pioneering studies related to Neo-Assyrian relief sculpture and seals, Phoenician and Syrian ivory and bronze production, and inter-polity connections across the various cultures of first millennium B.C.E. from the Aegean to Iran. Consistent threads are an emphasis on the potential for art historical analysis to yield 'history' in the broadest sense; the importance of making the theoretical frame of interpretation explicit; and the necessity of textual evidence being brought to bear upon elements of formal analysis and archaeological context. "These beautifully produced volumes bring together essays written over a 35-year period, creating a whole that is much more than the sum of its parts...No library should be without this impressive collection." J.C. Exum